Thermoregulatory behaviour limits local adaptation of thermal niches and confers sensitivity to climate change. (12th February 2015) - Buckley, Lauren B.; Ehrenberger, Joseph C.; Angilletta, Michael J.
Summary: Thermoregulation buffers environmental variation, which enables a species to persist during climate change but ultimately hinders adaptation of thermal tolerance by weakening selective pressure. We used a model of optimal thermal physiology to demonstrate how thermoregulatory behaviour limits local adaptation of thermal physiology in a widespread group of lizards, the Sceloporus undulatus complex. Empirical data for seven populations demonstrates conservatism of thermal tolerance, consistent with the model's prediction in the case of effective thermoregulation. In an eighth population, from a region where thermoregulation should be less effective, we observed greater heat tolerance and poorer cold tolerance, as predicted by our model. Biophysical modelling indicates that lizards can avoid heat stress through thermoregulation in the coming decades but will ultimately experience an abrupt decline in the effectiveness of thermoregulation. In this scenario, thermoregulators will suffer a greater loss of performance in future climates than thermoconformers will, unless heat tolerance can evolve in a few generations. Our analyses raises a concern that behavioural plasticity, while beneficial in the short term, will ultimately limit the physiological adaptation required to endure a warming climate. Abstract : Lay Summary